2012
DOI: 10.1177/1753193412469012
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis and related factors in patients with traumatic hand injury

Abstract: The aim of this study was to measure the direct and indirect costs and factors influencing these costs in patients presenting following traumatic hand injury. We assessed patients aged 18-65 years who were in work. Hand injury severity and functional status were assessed. Direct costs, including medical care expenses, and indirect costs, including lost productivity, were calculated. Seventy-nine patients of a mean age of 32 years were included. The mean direct cost for each patient was $1772 (47% of total cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 23 publications
0
31
1
4
Order By: Relevance
“…We have shown that these injuries are associated with a considerable volume of visits (over 5% of all ED visits) within the health network. This finding is significantly less than the estimated 10–30% proposed in international literature . One possible explanation for our finding is that we conducted our study from the perspective of one health network.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…We have shown that these injuries are associated with a considerable volume of visits (over 5% of all ED visits) within the health network. This finding is significantly less than the estimated 10–30% proposed in international literature . One possible explanation for our finding is that we conducted our study from the perspective of one health network.…”
Section: Discussioncontrasting
confidence: 75%
“…Injuries to the hand and wrist are common, with reports suggesting that they account for between 10% and 30% of all ED presentations, and typically affect young and economically productive populations . Although most uncomplicated injuries will recover fully, accurate assessment and treatment are vital as mismanagement can result in delayed recovery and potential long‐term disability at a significant cost to the individual, healthcare system and society …”
Section: Introductionmentioning
confidence: 99%
“…Ülkemizde yapılan farklı çalışmalarda olguların %32,8-72,1'inin iş kazası, %19-25'inin ev kazaları, %8,5-9'unun ise kendine zarar verme sonucu geliş-tiği belirtilmiştir (2,5,9). Putter ve arkadaşları (13) Hollanda'da yaptıkları çalışmada maliyeti en yüksek olan yaralanma sebebini ev kazaları olarak tanım-lamışlardır.…”
Section: Tartıșmaunclassified
“…El ve el bileği yaralanmaları yaygın olarak görülen bir sağlık problemidir. Acil servis başvu-rularının yaklaşık %10-20'sini ve tüm yaralanmaların yaklaşık %6.6-28.6'sını oluşturmaktadır (3)(4)(5). Yaralanmaların çoğu erkeklerde ve aktif çalışan yaş aralığında görülmektedir.…”
unclassified
See 1 more Smart Citation